Pengaruh Senam Hamil terhadap Nyeri Punggung pada Kehamilan Trimester III - Nilam, Nur; Sholihah, Andri Nur Sholihah (Jurnal Kesehatan, 2024)
During the adaptation process, mothers often experience discomfort, even though it is physiological, but it is still necessary to provide prevention and treatment regarding several discomforts in pregnant women entering the third trimester. During pregnancy, 90% of women can experience back pain, making back pain the most common minor disorder in pregnancy. Efforts that can be made to prevent and treat back pain in pregnant women are by exercising during pregnancy. The aim of this study was to determine the effect of pregnancy exercise on reducing back pain in the third trimester of pregnancy. This research method uses pre-experiment research with a one group pretest posttest research design. The data collection technique used purposive sampling, the sample used was 15 pregnant women who experienced back pain. The materials and tools used in this research were the FPS-Revised pain observation sheet and maternal demographic data. Data analysis used the non-parametric Wilcoxon sign rank statistical test with a result of 0.000 which means that there is a significant influence of the influence of pregnancy exercises on the reduction of back pain in the third trimester of pregnancy. Thus, it can be concluded that there is an influence of pregnancy exercise on reducing back pain in the third trimester of pregnancy. It is hoped that pregnant women will do pregnancy exercises regularly to reduce back pain during pregnancy.